Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12889-016-3768-4
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a Housing First adaptation for ethnic minority groups: findings of a pragmatic randomized controlled trial

Abstract: BackgroundLittle is known about the effectiveness of Housing First (HF) among ethnic minority groups, despite its growing popularity for homeless adults experiencing mental illness. This randomized controlled trial tests the effectiveness of a HF program using rent supplements and intensive case management, enhanced by anti-racism and anti-oppression practices for homeless adults with mental illness from diverse ethnic minority backgrounds.MethodsThis unblinded pragmatic field trial was carried out in communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 36 publications
2
50
1
1
Order By: Relevance
“…This choice may contribute to HF participants living in housing and neighborhoods in which they feel at home and develop a sense of belonging. In contrast with our study, the multi-site study did not show HF participants experiencing greater improvements in psychological integration than TAU for either individuals with high needs [19] or moderate needs [45]. Previous research has shown residents living in small cities to report higher levels of a sense of belonging than residents living in larger cities [46].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This choice may contribute to HF participants living in housing and neighborhoods in which they feel at home and develop a sense of belonging. In contrast with our study, the multi-site study did not show HF participants experiencing greater improvements in psychological integration than TAU for either individuals with high needs [19] or moderate needs [45]. Previous research has shown residents living in small cities to report higher levels of a sense of belonging than residents living in larger cities [46].…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, in the same trial, HF with ICM, when compared to TAU for individuals with moderate level of needs, produced greater improvements in overall quality of life and related to living situation, safety, and leisure [45]. In our study, HF participants with a mix of moderate and high level of needs and receiving ACT reported greater improvements of quality of life than TAU over the full 24-month study.…”
Section: Discussionmentioning
confidence: 51%
“…In fact, the existing literature provides little evidence that the Housing First intervention improves other non-housing outcomes, such as quality of life, physical community integration, psychological community integration or mental health. [52] Homeless individuals with major depressive episode, mood disorder with psychotic features, and substance disorder were more likely to remain persistently food insecure over the study period. We also found co-occurring disorders played a major role in food insecurity trajectories.…”
Section: Plos Onementioning
confidence: 91%
“…The most commonly used measure was the Community Integration Scale (Aubry & Myner, 1996; n = 3; 14.3%), modified by Patterson et al. (2014) and subsequently used as modified scale in other studies (O'Campo et al., 2016; Patterson et al., 2014; Stergiopoulos et al., 2016). Other standardised scales used in full or in part to measure CI included: Lehman's Quality of Life Interview (Lehman, 1983; n = 2; 9.5%; O'Connell et al., 2017; Wood et al., 1998); Social Provisions Scale (Cutrona & Russell, 1987; n = 2; 9.5%; Pankratz et al., 2017; Stewart et al., 2009); ASR (Achenbach, 1997; n = 2; 9.5%); Multnomah Community Ability Scale (Hendryx, Dyck, McBride, & Whitbeck, 2001; n = 1; 4.8%; Aubry et al., 2016); UCLA‐LS‐R (Russell et al., 1980; n = 1; 4.8%; Stewart et al., 2009); SCS‐R (Lee et al, 2001; n = 1; 4.8%; McCay et al., 2011); MOS‐SSS (Sherbourne & Stewart, 1991; n = 1; 4.8%; Boisvert et al., 2008); and ASI (McLellan et al, 1992; n = 1; 4.8%; Devine et al., 1997).…”
Section: Resultsmentioning
confidence: 99%